Recent Cyprididae and Ilyocyprididae (Crustacea: Ostracoda) from Lake Biwa, Japan, including a summary of the lake’s ostracod fauna - Smith, Robin J.; Janz, Horst; Okubo, Ichiro (Zootaxa, 2011)
Sampling between 1999 and 2007 of the recent ostracod fauna of Lake Biwa, an ancient lake located in Japan, produced ten Cyprididae and one Ilyocyprididae species. One Cyprididae species, belonging to the genus Ilyodromus is described herein, Ilyodromus intermedius Okubo n. sp., and Bradleytriebella lineata (Victor & Fernando, 1981c) is redescribed. One Cyprididae species is a new record for Japan, namely Stenocypris malayica Victor & Fernando, 1981a, while seven others are new records for Lake Biwa. The family Ilyocyprididae is represented by only one species in Lake Biwa, Ilyocypris salebrosa Stepanaitys, 1960. The Lake Biwa population of this species is the first record of males and they are described in this paper. Including this study, forty ostracod species have now been reported from Lake Biwa. Most species (70%) were found at depths of less than 1 meter. Only four species were found below 44 m, the mean depth of the north basin.